Diagnostic Accuracy of Tissue Impedance Measurement Interpretation for Correct Veress Needle Placement in Canine Cadavers12. Issue 5 (1st February 2013) - Whittemore, Jacqueline C.; Mitchell, Amanda; Hyink, Sara; Reed, Ann
Abstract: Objective: To establish the diagnostic accuracy of tissue impedance measurement interpretation (TIMI) for determining correct versus incorrect Veress needle placement. Study Design: Prospective, randomized, blinded trial. Study Population: Canine cadavers (n = 20). Methods: Two laparoscopists (1 experienced, 1 novice), blinded to tissue impedance measurement results, placed reusable Veress needles in canine cadavers in a randomized order. A 3rd individual interpreted impedance measurements as consistent with correct or incorrect Veress needle placement. Veress needle tip locations were marked by injecting contrasting colors of India ink. Tissue dissection was performed to localize ink. Sensitivity, specificity, accuracy, precision, and kappa statistics for TIMI for placements by the experienced and novice laparoscopist were determined. P < .05 was considered significant. Results: TIMI identified 29/33 correct and 7/7 incorrect placements, respectively. Impedance measurement interpretation had 87.9% sensitivity, 100% specificity, 90% accuracy, and 100% precision overall. Agreement between TIMI and Veress needle location was moderate (kappa 0.50, P = .01) for placements by the experienced laparoscopist and very high (kappa 0.88, P < .01) for the novice laparoscopist. Conclusions: Diagnostic accuracy of TIMI for Veress needle placement was higher than has been reported for other tests, and TIMI had a shallow learning curve. TIMI successfully detected all incorrect Veress needle placements. Further prospective evaluation of Veress needle placement with and without TIMI is warranted to determine if its use increases operator detection of inappropriate Veress needle placements or decreases installment phase complication rates.